Obraz Czechosłowacji w karykaturach opublikowanych na łamach czasopism satyrycznych „Mucha” i „Szpilki” w latach 1945-1948 - Ślęzak, Jolanta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The author presented a vision of Czechoslovakia created by Polish caricatures. The main source was caricatures which were published in Polish satirical magazines “Szpilki” and “Mucha” from 1945 to 1948. The author used quantitative analysis which allowed plots portrayed within the caricatures to be caught. The paper is composed of three parts which contain analysis of the particular caricatures. The first one showed analysis of caricatures which created Czechoslovakia as an enemy of Poland. That vision was connected with border conflicts between the neighbouring countries. The second third parts contain caricatures which presented Czechoslovakia as a friend of Poland. The way Czechoslovakia was presented resulted from the fact that both Poland and Czechoslovakia were members of the socialist bloc countries. The way Czechoslovakia was presented changed simultaneously with the changes in the relationships between the neighbouring countries. It was also dependent on the wider context – dependence of both countries on the USSR.
THE IMAGE OF CZECHOSLOVAKIA IN CARICATURES WHICH WERE PUBLISHED IN SATIRICAL MAGAZINES „MUCHA” AND „SZPILKI” FROM 1945 TO 1948
Keywords: caricature; Polish-Czechoslovakian relationships; visual propaganda